The interaction between the digital and material world: transnational practices among high tech Indian immigrant workers - Sarmistha, Uma (Kansas State University, 2013)
Asian-Indians represent an important component of the professional and ‘high-tech’ workers in the U.S. Research on this population has found that majority of these workers are temporary workers working on a contractual jobs. Further, it is not unusual for Indian immigrant workers to get married and have children while in the U.S. As such, they must learn to negotiate the U.S. cultural terrain in both their place of work and home life. This provides the potential that they will become transnational by developing identities and engaging in cultural and social practices from two different nations, India and the U.S. This dissertation investigates the nature and extent of transnational practices adopted by high-tech Indian workers employed by U.S. firms on a temporary work visa. In summary, the purpose of this research is to explore and describe the prevalence and practice of transnationalism among Indian high-tech workers employed by U.S. firms on a temporary work visa and its impact on their lives.  The study uses a mixed-methods research (Ivankova, Creswell and Stick, 2007), where quantitative survey and qualitative data collection are used in single study to understand the stated research problem. Also, as there is no formal list of Indian IT professionals working in the U.S. at contractual jobs, the data collection will be carried out through the non-random chain-referral sampling technique. A detailed survey and personal interview will be used to measure various micro aspects of these workers' lives including consumption patterns, recreational choices, socialization, cultural beliefs and family dynamics. The study reveals that the temporary stay of these professionals in the U.S. along with their families necessitates day-to-day negotiations between two cultures in terms of their food, clothing, recreation, and daily activities creating a transnational life style for these young professionals. The responses reflect the inner struggle of these professionals between their long-term goals of settling in India with their families and the current material life in a far-away land of opportunity. On one hand, the dualism of living in the U.S. as an Indian is demonstrated in this study by the convergence of the disparate elements of both aspects of their lives, work, incomes and remittances; on other hand, family, social life, religion, consumption patterns, and recreation activities provide the glimpse of a dual life. All of these cultural and social practices can be considered as the combination of transnationalism from ‘above’ and ‘below’ as noted by Smith and Guarnizo (1998). Transnational activities at the work place, which is forced by the work culture of the MNCs that employ them, can be considered as ‘transnationalism from above’. Simultaneously, being bi-lingual at home, cooking and eating Indian and Western food, socializing with Indian and American friends outside work, and all those cultural activities they perform on a day-to-day basis, indicates ‘transnationalism from below’. Overall, through this study, I have described important aspects of the transnational lives of Indian IT professionals, who try to maintain a fine balance between faster assimilation of American culture which might help them at the work place while simultaneously retaining much of their ‘Indian-ness’ so that going back to India never poses a problem when their visa expires. In a way, the lives of this particular group of professionals can be viewed as those of temporary-enclave residential workers.
Keywords: Transnationalism; Temporary workers; Asian Indian IT immigrants; Sociology (0626)